2011
DOI: 10.1007/s00464-011-1945-1
|View full text |Cite
|
Sign up to set email alerts
|

Management options for symptomatic stenosis after laparoscopic vertical sleeve gastrectomy in the morbidly obese

Abstract: Symptomatic short-segment stenoses after LSG may be treated successfully with endoscopic balloon dilation. Long-segment stenoses that do not respond to endoscopic techniques may ultimately require conversion to Roux-en-Y gastric bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(78 citation statements)
references
References 35 publications
0
69
0
7
Order By: Relevance
“…Endoscopic dilatation is an invaluable tool used in this setting of a short segment stenosis. 25 Successive treatments in 4-to 6-week intervals are adequate to treat stricture and ameliorate patient symptoms. In contrast, long segment stenosis and failure of endoscopic management demands a surgical intervention.…”
Section: Stricturementioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic dilatation is an invaluable tool used in this setting of a short segment stenosis. 25 Successive treatments in 4-to 6-week intervals are adequate to treat stricture and ameliorate patient symptoms. In contrast, long segment stenosis and failure of endoscopic management demands a surgical intervention.…”
Section: Stricturementioning
confidence: 99%
“…These investigators reported successful results with this treatment. Parikh and colleagues 25 reported an incidence of 3.5% of symptomatic stenosis following LSG in their series of 230 patients; 2 patients required conversion to a Roux-en-Y gastric bypass owing to failure of endoscopic management.…”
Section: Stricturementioning
confidence: 99%
“…This can be equated to twisting a straight balloon where there is a twist at the incisura. 9 Baumann T et al recommended to do a proper posterior dissection of the stomach in sleeve gastrectomy in order to achieve a symmetric stapling of the posterior and anterior wall to avoid twisting of the remnant stomach tube.…”
Section: Resultsmentioning
confidence: 99%
“…This functional stenosis makes it difficult for gastric contents to pass through, in spite of the easy passage of the endoscope or balloon dilator through the narrowed area. 9 Recently It has been reported that loss of abdominal ligament fixations along the greater curvature of the stomach may be implicated, so regaining normal anatomical fixation of the greater curvature to the gastrocolic ligament and gastrosplenic ligament may solve this problem and this will be the cornerstone of our study.…”
Section: Introductionmentioning
confidence: 99%
“…Die Auswertung der in der nationalen Datenbank gespeicherten Fälle von 2005 bis 2010 verzeichnet 2734 (53,6 %) LSA, 1587 (31,1 %) CSA und 783 (15,3 %) HSA [17]. Gonzales et al [9] fanden bei 108 Fällen mehr Strikturen nach CSA (31 %) als nach HSA (3 %) oder LSA (0 %), wobei die Anzahl der ausgewerteten Patienten schwankt (n = 87 HSA; n = 13 CSA; n = 8 LSA).…”
Section: Epidemiologieunclassified